Assessment of Soil Properties and Nutrients Status in three Horticultural Land use System of Coastal Odisha, India - Srinivasan, R.; Singh, S. K.; Nayak, D. C.; Dharumarajan, S. (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted to examine the different horticultural land use system on soil properties and nutrients status in Odisha coastal plain. Soil samples were collected from major three land uses (viz. cashew, mango and arecanut) in different depths (0–25, 25–50, 50–75, and 75–100 cm) and analyzed for soil physical and chemical properties. The different landuse are significantly varied with soil properties viz. pH, EC, CEC, AWC and rich in OC on surface (0–25 cm) soils. The available N content in surface and subsurface soils ranged from 85 to 259 and 40 to 221 kg ha-1. The greatest P content was 10.7 to 57.1 kg ha-1 in the surface layer of arecanut and the least was 3.7 kg ha-1 in cashew. K content in surface and subsurface soils ranged from 57 to 438 and 14 to 553 kg ha-1. Nutrients index values N was low (1.0), P was low to medium (1.0–1.6) and K was categorized medium in all the land use. The content of Fe and Mn were sufficient (>4.5 and >2 mg kg-1) in all landuse. The Cu was rich in surface soils (1.76–3.57 mg kg-1) of arecanut. Zinc content varied from 0.68 to 1.68 mg kg-1 in the surface to subsurface layers of soils respectively. Pearson’s correlation matrix revealed significant positive correlations of soil properties with fertility indices.